Effect of childhood adversities on alcohol problems is mainly mediated by depression. (15th May 2018) - Salokangas, Raimo K. R.; From, Tiina; Luutonen, Sinikka; Salokangas, Henri R. W.; Hietala, Jarmo
Abstract : Background and Objectives: We aimed to study how five childhood adversities and trauma (CAT) core domains: emotional abuse (EmoAb), physical abuse (PhyAb), sexual abuse (SexAb), emotional neglect (EmoNeg), physical neglect (PhyNeg), associate with alcohol problems (APs), and whether there are any gender differences in these associations. Methods: Altogether, 690 adult participants drawn from the general population completed a mailed questionnaire, including the trauma and distress scale, as an indicator of CAT, and questions concerning sociodemographic background, depressive symptoms, and APs. Results: In univariate analyses, male gender, middle age, divorced/separated marital status and lower education, frequency of use of alcohol, previous treatment for mental problems, as well as depressive symptoms and CAT domain scores were associated with APs. Of the CAT domains, females reported more EmoAb and SexAb than males, but there was no gender difference in other CAT domains and depressive symptoms. In multivariate analyses, when the effects of background characteristics were controlled, CAT sum and all its domains had indirect effects via depressive symptoms on APs with no significant direct effect except in females, in whom PhyAb and SexAb associated directly with APs even when the effects of other CAT domains were taken into account. Conclusions and Scientific Significance: All CAT domains associate extensively with APs. Generally, their effect on APs is mainly mediated via depressive symptoms. In females, PhyAb and SexAb also have a considerable direct effect on APs. In treating individuals with CAT experiences and alcohol problems, treatment of depression is also important. (Am J Addict 2018;27:391–399)